Pilot Study of the Just Right Challenge Feeding Protocol for Treatment of Food Selectivity in Children. - Suarez, Michelle A.; Bush, Elsie (Open Journal of Occupational Therapy (OJOT))
Background. This pilot study investigated the Just Right Challenge Feeding Protocol, a multicomponent treatment protocol for food selectivity that combines escape extinction, positive reinforcement, and systematic desensitization. Method. This study used a single-subject, multiple-baseline-across-participants design to investigate whether treatment produced increases in the food inventories for seven children. All of the children in the study started with parent report of fewer than 15 foods in their dietary repertoire. A sensory profile for each child provided information for treatment planning and interpretation of the results of the study. Results. Five out of the seven children accepted significantly more foods after a treatment latency period. These five children each had sensory profiles that indicated possible sensory overresponsivity. There was a statistically significant increase from baseline to the last treatment session on the mean number of foods on the inventory for the group. Conclusion. The Just Right Challenge Feeding Protocol is a promising treatment for increasing food acceptance for some children with food selectivity. It may be particularly helpful for children with food selectivity and sensory overresponsivity.